Inducible interleukin-1 gene expression in human vascular smooth muscle cells. - Libby, P (1986)
Interleukin-1 (IL-1) mediates many components of generalized host response to injury and may also contribute to local vascular pathology during immune or inflammatory responses. Because altered function of smooth muscle cells (SMC) accompanies certain vascular diseases, we tested whether SMC themselves might produce this hormone. Unstimulated SMC contain little or no IL-1 mRNA. However, exposure to bacterial endotoxin caused accumulation of IL-1 mRNA in SMC cultured from human vessels. Endotoxin maximally increased IL-1 beta mRNA in SMC after 4-6 h. The lowest effective concentration of endotoxin was 10 pg/ml. 10 ng/ml produced maximal increases in IL-1 beta mRNA. Interleukin-1 alpha mRNA was detected when SMC were incubated with endotoxin under "superinduction" conditions with cycloheximide. Endotoxin-stimulated SMC also released biologically functional IL-1, measured as thymocyte costimulation activity inhibitable by anti-IL-1 antibody. Thus, human SMC can express IL-1 beta and IL-1 alpha genes, or very similar ones, and secrete biologically active product in response to a pathological stimulus. Endogenous local production of this inflammatory mediator by the blood vessel wall's major cell type could play an important early role in the pathogenesis of vasculitis and arteriosclerosis.